Sumatran batik motif design and documentation using turtle graphics algorithm based on local wisdom - Ratnadewi, Ratnadewi; Prijono, Agus; Pandanwangi, Ariesa (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
Using the Turtle Graphic algorithm to digitize and develop Sumatra batik motifs is an innovative step in preserving local wisdom. This algorithm, which was originally used in graphics programming to educate children about computer concepts, is now being utilized to design and reproduce intricate and detailed batik motifs. The problem is that most existing batik motifs have not been digitally stored. Therefore, the purpose of the research here is to digitize Sumatra batik motifs using the Turtle Graphics algorithm. Turtle graphics utilizes command-based programming principles to draw geometric shapes. As an icon for North Sumatra Province, the basic motif of the existing water tower batik is the focus of this pattern accuracy. It is documented using a Python program that uses the turtle graphics algorithm, and a new Sumatran batik motif design is created from this basic motif. The benefits of research results with this approach are that designers can digitally modify and reproduce traditional batik motifs. This algorithm allows the drawing of patterns with high accuracy, making creating consistent and precise motifs easier. This digitization process also helps document and preserve batik motifs. The use of this technology not only speeds up the design process but also provides wider access to the younger generation and the international community to appreciate and learn about Sumatra batik. By integrating modern technology and local wisdom, the digitization of rare batik motifs has the potential to strengthen cultural identity and increase the economic value of traditional batik products. The specific steps in the motif digitization or pattern-making process are as follows: determine the motif to be digitized, select the starting point of the moving turtle, determine the turtle's direction of motion in relation to the curve to be formed, execute the program, and if the turtle curve does not move in the desired direction, change the program and execute again until the turtle motion curve matches the desired curve. This process is repeated multiple times.